Evaluation of the quality of prescription orders in a tertiary health-care facility in Southeastern Nigeria - Nneka Uchenna Igboeli; Chibueze Anosike; Onyinye Blessing Ukoha-Kalu; Ebere Emilia Ayogu (Wolters Kluwer Medknow Publications, 2018)
Background: Prescription orders serve as a source of communication linking the physician, patient, and pharmacist. However, inappropriate prescriptions may result in medication errors, thus may worsen clinical outcome and economic burden of the patient. Therefore, this study aimed at evaluating the quality of prescription orders in terms of completeness, appropriateness, and authenticity at a tertiary health-care facility in Nigeria. Methods: A retrospective, cross-sectional review of prescription orders from the Outpatient Pharmacy of the Enugu State University Teaching Hospital, Parklane, Enugu, Nigeria. Data collection was done using a data collection form adopted from the World Health Organization (WHO) guideline for good prescription practice. This study was carried out between July and December 2012. Descriptive statistics were used for the purpose of analyzing extracted data. Results: Five hundred prescriptions were used in the study. Prescriptions containing the name of the prescribers and patients name and address were 0.8% and 97.8%, respectively. The age and body weight of the patients were documented in 17.6% and 38.8% of the prescriptions in that order. Thirty-five percent of the drugs were written in generic names, while most of the prescription orders had well-documented dosage form (95.6%), date of prescription (90.6%), and prescriber's initials or signature (83.0%). The direction for use by the physician was clearly written in <1½ (38.8%) of the prescriptions. Conclusion: Our findings suggest deviation from complete adherence to the basic principle of good prescription writing recommended by the WHO among medical practitioners in the study setting.